2006
DOI: 10.1029/2006eo390002
|View full text |Cite
|
Sign up to set email alerts
|

Toward a risk assessment of central Aegean volcanoes

Abstract: PAGES 401,407Active tectonic processes along the AfricanEurasian collision zone are associated with catastrophic events including earthquakes, major volcanic eruptions, and tsunamis. Understanding how these processes can affect the eastern Mediterranean is of increas ing scientific and public interest. The region includes a frequently crossed international sea traffic corridor and dense population centers. Furthermore, most of the small vol canic islands in the Aegean are major tourist attractions that contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 2 publications
1
27
0
3
Order By: Relevance
“…This assumption is in very good agreement with recent independent geophysical (Huebscher et al, 2006, Hensch et al, 2008, seismological (Bohnhoff et al, 2006) and geothermal (Sigurdsson et al, 2006) results for the same area. The interpretation of the NE-SW cross-sections shown in Figures (12a) and (12b) should be considered with caution.…”
Section: Tomographic Results -Conclusionsupporting
confidence: 80%
“…This assumption is in very good agreement with recent independent geophysical (Huebscher et al, 2006, Hensch et al, 2008, seismological (Bohnhoff et al, 2006) and geothermal (Sigurdsson et al, 2006) results for the same area. The interpretation of the NE-SW cross-sections shown in Figures (12a) and (12b) should be considered with caution.…”
Section: Tomographic Results -Conclusionsupporting
confidence: 80%
“…56 and during the ‘ATLANTIS FOUND' project in 2015. The respective sources for the high-resolution seismic profiling system were a 45/105.…”
Section: Methodsmentioning
confidence: 99%
“…Huebscher et al (2006) have been able to observe in seismic reflection profiles two cone-like volcaniclastic deposits, which indicate that the Kolumbo volcano evolved from at least two eruptions. Bohnhoff et al (2006) report that, the highest seismic activity in the area has been observed along the SW-NE striking Santorini-Amorgos zone.…”
Section: Introductionmentioning
confidence: 92%
“…The interpretation of this profile suggests that at least one older volcanic cone exists and is located underneath the present one, indicating that Kolumbo has been active at least once, prior to the 1650 eruption (see also Huebscher at al., 2006). Layered or massive lava flows form the lower part of the present Kolumbo cone and are displayed as stratified, high amplitude, subhorizontal reflectors on the profile.…”
Section: The 15mentioning
confidence: 99%